Dewan Komisaris Independen Sebagai Pemoderasi Pengaruh Financial Distress pada Kecepatan Publikasi Laporan Keuangan - Putri, Ni Putu Wanda Anggeliana; Latrini, Yenni (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p21, 2018)
Financial statement is an important instrument, because it can reduce the asymmetry of information that occurs between companies and the public. The velocity of publication of the financial statements may affect the users trust in the financial statements, this is because the information contained in the financial statements is required by the user to  take an economic decision. The purpose of this study is to prove empirically and explain the impact of financial distress on the velocity of publication of financial statements with independent board of commissioners as a moderator variabel. This research was conducted at company of consumer goods industry sector which listed in Bursa Efek Indonesia in 2012-2016. The samples of research taken with non probability sampling method with purposive sampling technique, so that obtained sample of 22 companies with 110 observation. Moderate Regression Analysis is a data analysis technique to obtain the results, the result of research is financial distress have positive effect on the velocity of publication of financial report and independent board of commissioner weaken the effect of financial distress on the velocity of publication of financial statement. Keywords:  independent commissioners, financial distress, velocity of publication of the financial statements